ANALISIS NILAI KALOR SERTA LAJU UAP DARI BOILER DENGAN VARIASI KOMPOSISI BERAT SAMPAH ORGANIK DAN ANORGANIK PADA PLTSA - Satria Adi Luhur, Dewa Putu; Indra Partha, Cok Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2025.v12.i01.p5, 2025)
Bali Province produces 2,814.89 tons of waste per day or 1,027,433.75 tons per year in 2023. Waste is a problem that is still difficult to overcome. Badung Regency is one of the largest suppliers of waste in Bali Province, in Badung Regency, the waste produced reaches 195,222.46 tons per year. TPST 3R Legian Kaja is one of the waste management facilities located in Badung Regency. This TPST is capable of managing 16 tons of waste per day, one of the methods used is incineration or burning waste. During the combustion process, the heat energy produced can actually be used to generate electricity. However, the heat energy produced is not utilized, so there is potential for waste of heat energy. This study aims to determine the steam pressure produced by a boiler with a capacity of 9 liters of air and 10 kg of waste variation in the Waste Power Plant (PLTSa) prototype. The method used in this study is quantitative descriptive. In this study, using 3 variations of composition from 10 kg of waste, the highest calorific value was obtained from the variation of 7 kg of organic waste + 3 kg of inorganic waste, using a boiler with a capacity of 9 liters of air and a steam pressure of 3 bars, a power of 405 Watts was obtained.